Empowering Students Through Technology: Evaluating A Project-Based Learning Approach to Address Clean Water Scarcity - Indiwara, Rendi (South Sulawesi Education Development (SSED), 2025)
This study applies a goal-free evaluation model to examine the implementation of Project-Based Learning (PBL) in addressing clean water scarcity through the use of NodeMCU ESP8266 and Internet of Things (IoT) technology. Conducted with vocational students at SMKN 1 Kasongan, the project involved designing a water quality monitoring system in response to local river pollution caused by illegal mining. Data were collected through observations, interviews, reflections, and product evaluations, and then analyzed thematically. The findings show that students developed technical skills in sensor integration, programming, and real-time data visualization, alongside non-technical skills such as collaboration, communication, and problem-solving. Unexpected outcomes also emerged, including greater environmental awareness, community engagement, and intrinsic motivation to expand the project. This study highlights the value of PBL in vocational education, recommending its wider adoption to link technology with real-world issues, and contributes theoretically by demonstrating the effectiveness of goal-free evaluation in capturing emergent learning outcomes.